Antigen Processing by Macroautophagy for MHC Presentation - Munz, Christian (Frontiers in Immunology, 2011)
T cells recognize antigen fragments, presented to them by MHC molecules. It lies in the interest of the immune system to display a maximal diversity of these peptides and utilize all catabolic processes to generate them. Macroautophagy, a pathway that delivers cytoplasmic constituents for lysosomal degradation, is no exception. In recent years, it has become apparent that macroautophagy assists in intra- and extracellular antigen processing for MHC class II presentation to CD4+ helper T cells. Surprisingly, however, macroautophagy also assists in antigen packaging for better cross-presentation on MHC molecules of bystander cells, which could be consistent with its role in unconventional protein secretion. These three pathways of antigen processing for MHC presentation via macroautophagy will be discussed in this review and cell biological aspects will be high-lighted that might explain, how the molecular machinery of macroautophagy might assist these diverse antigen processing pathways.